Image of seismological anomaly before the February 18, 2020 Changqing M4.1 magnitude earthquake. Issue 1 (April 2021) - Zhao, Jinhua; Cui, Huawei; Li, Cuiqin; Gai, Dianguang
Abstract: An earthquake of magnitude M 4.1 occurred in Changqing County, Shandong Province (36.46°N, 116.65°E) on February 18, 2020. In this paper, we found from the image analysis of seismic activity and wave velocity ratio calculation before this earthquake that the magnitude M 4.1 (No special markings on the magnitude of the earthquake: M for magnitude 5 (including magnitude 5) and above, M L for below magnitude 5) in the 1-year scale before the Changqing M 4.1 earthquake, inland Shandong and In the Bohai Sea, there is an orderly distribution of magnitude 2 earthquakes, multiple small earthquake sequences, a concentration with active of magnitude 3 earthquakes, the Changdao "earthquake window" "open" several times, and an abnormally low value of wave velocity ratio etc. Phenomena.